O processo decisório na administração municipal de Franca-SP: o planejamento estratégico e o orçamento participativo (em dois mandatos consecutivos gestão 1997-2002) - Sypryani, Ulisses Luiz (Universidade Federal de São Carlos, 2004)
This study analyses the changes decurrents with the implementation of strategic planning in the Municipal Administration of Franca, in two consecutive terms (1997- 2002). In that perspective, three categories of analysis that are inter-related are examined (FREY, 2000). The first of them pertains to the decision-making process of the administration, the second one is about administrative structure and, lastly, the material content analysis of the participatory budgeting (PB) demands. The sources of consultation used to get the information are documents, decrees and meeting minutes, project lists of PB (executed, in progress and not executed), statements with managers and technicians of administration and with counselors of PB, that participated in two terms, and the participant observation (research author as the observer and participating actor). The results gotten refer to: (1) changes in the decision-making process of municipal administration, (2) changes in the administrative structure, (3) number of projects implemented and not implemented before and after the implementation of the strategic planning, (4) changes in the administrative conducts of managers and technicians from various areas in elaborating and in monitoring projects demanded in PB, (5) perception of counselors of PB in relation to the participation and accomplishment of PB demands and (6) in physical and territorial localization of PB demands in Franca city. The results achieved indicate that the use of concepts and a few instruments of strategic planning in municipal administration permitted advances in attending the PB demands, in view of democratization of planning and municipal public administration.
Keywords: Engenharia urbana; Administração pública; Planejamento estratégico situacional (PES); Gestão pública; Gestão participativa; Metodologias participativas; ENGENHARIAS